INNOVATION CHALLENGES OF VILLAGE-OWNED ENTERPRISES - Gabriella Hanny Kusuma; P. Didit Krisnadewara (KINERJA, 2019)
The research intended to explore the innovation challenge of village-owned enterprises. The challenge focus on managerial and innovation capabilities of village owned enterprises. This study uses a Community-Based Research (CBR). This approach is used to find out how far from the community at the micro, mezzo, and macro level that can help the village as a whole. To collect the data, this research used observation, personal in-depth interview, and focus group discussion. The village-owned enterprises need innovation for their sustainability. This research found 3 major challenges for the village-owned enterprises innovation. The challenges are a) Lack of Knowledge and skills, b) Financial and infrastructure limitation, c) Social – professional conflict. Human factor is the main challenge that needs to be solved by village-owned enterprises. The village-owned enterprises should overcome these challenges hence they can be spared from Innovation myopia. This research conducted in the village-owned enterprises which dominated by Javanese culture. This research also conducted in the service sector. In the future, exploring innovation challenge in the village-owned enterprise which has different culture would be interesting. The future research also can explore innovation challenge in the manufacturer village-owned enterprises. This paper shows the innovation challenge in village-owned enterprises which has unique characteristic.Keywords: Badan Usaha Milik Desa, Bumdes, innovation challenges, sustainability, village-owned enterprises